Reprints of Rare Papers on Mollusca: George W. Tryon, Jr. (1873) Land and Freshwater Shells of North America. Part IV. Strepomatidae (American Melanians) Smithsonian Miscellaneous Collections 253. Continued from Sterkiana no. 24; Reprinted with the Permission of the Smithsonian Institution - George W. Tryon (Hello World!, 1967)
Of the two remaining monographs, Part IV is given in the following pages, as prepared by Mr. G. W. Tryon, Jr., and will, it is hoped, tend to facilitate the study of a very intricate group, little understood. No special arrangement has been made by the Institution in reference to a monograph of the Unionidae (which would form a Part VI) since the many illustrated papers and synopses of the group, published by Mr. Isaac Lea. in the Memoirs of the Academy of Natural Sciences, and of the American Philosophical Society, as well as printed privately, render this less necessary. The present work by Mr. Tryon, therefore, completes the series of works on "Land and Fresh-water Shells of North America," as originally contemplated by the Institution. (Cont.)